(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted on hospital waste generation in Mymensingh municipality and also its management technique. Data was collected through questionnaire interview from local residents, superintendents, nurses, observation and secondary sources. The results revealed that wastes are collected every alternative day and though sometime in irregular basis. Hospital wastes causes different health hazards like bad smell, infestation of animals, diarrhoea, skin diseases etc. due to irregular collection, unsafe handling, disposal, storage, transportation and finally dumped with municipal wastes. Shortage of dustbin is common in every hospitals and clinics in Mymensingh municipality. The study also revealed that 1500-2000 kg wastes were generated per day in Mymensingh municipality area in which 25% infectious and 75% non- infectious. These huge amount of wastes could be treated or disposed by the process like incineration, deep-burial, local autoclaving, micro waving, disinfections destruction & drugs disposal in secured landfills, chemical treatment etc. J. Environ. Sci. & Natural Resources, 8(1): 135-138 2015